The occurrence of multidrug-resistance organisms of ESBL/AmpC-producing Escherichia coli, Klebsiella oxytoca, and Kluyvera spp. isolated from the environment of chicken slaughterhouses in Pondok Rumput, Bogor, Indonesia: Keberadaan bakteri multiresisten Escherichia coli penghasil ESBL/AmpC, Klebsiella oxytoca dan Kluyvera spp. diisolasi dari lingkungan ayam rumah potong hewan di Pondok Rumput, Bogor, Indonesia - Kalanjati, Woro Wulandari; Lukman, Denny Widaya; Sudarwanto, Mirnawati (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
In the last few years, multidrug resistant bacteria increased significantly and contaminated chicken carcass through production chain. This study identified the presence of ESBL/AmpC-producing Enterobactericeae collected from the environment of chicken slaughterhouses. Samples were taken before slaughtering process from several points of determined locations. From a total of 84 samples tested, 30 isolates were positive of Enterobactericeae comprising of 22 isolates of E. coli, 6 isolates of Klebsiella oxytoca, and 1 isolate of Kluyvera spp. Confirmation test of ESBL/AmpC phenotypic and antibiotic resistant test to 18 kinds of antibiotics were conducted using MASTDISCS D68C commercial kit and Kirby-Bauer disc diffusion susceptibility test with CLSI (2014) interpretation. All of isolates showed resistance to penicillin, ampicillin, amoxicillin, cefotaxime, cefpodoxime, ceftazidime and some isolates show resistance to streptomycin, gentamicin, trimethoprim-sulphametoxasol, tetracycline, kanamycin, doxycyclin, colistin sulphate, cephalothin, neomycin and polymyxin  B. This study demonstrated the existence of ESBL/AmpC-producing  Enterobactericeae that were found on the carcasses container, offal container, floors of carcasses, offal handling area, knives and feathers puller machine. The existence of resistant bacteria in the environment of chicken slaughterhouse can lead to occurrence of antibiotic resistant and transmission of resistance genes to other bacteria that could spread to the carcass that was potentially harmful to humans.